Small incision reduction and external fixation for the treatment of delayed over fourteen days supracondylar humeral fractures in children - Liu, Shuai; Peng, YingYing; Liu, JiaTong; Ou, ZiXuan; Wang, ZeZheng; Rai, Saroj; Lin, WeiFeng; Tang, Xin (Frontiers in Pediatrics, 2022)
Background: Supracondylar humeral fractures (SHF) are the most common type of fracture occurring at the distal humerus in children. In patients with delayed presentation of SHF, closed reduction is challenging to achieve with traditional reduction maneuvers. This study aimed to report the clinical results of pediatric SHF delayed over 14 days treated by closed reduction with a minimally invasive technique and external fixation and evaluate the efficacy of this technique. Methods: Between October 2010 and September 2018, children with delayed presentation of supracondylar humeral fractures over 14 days were retrospectively included in this study. The patients received closed reduction with a minimally invasive technique followed by external fixation. The demographics and radiographic data were collected. The Mayo Elbow Performance Score (MEPS) and the Flynn criteria were used to evaluate the clinical outcomes of treatments. Results: A total of 11 children (aged 4-13 years) with delayed presentation (range, 14-22 days) were recruited. They received surgery using closed reduction with a minimally invasive technique followed by external fixation. None of the surgery was done with the open method. After surgery, the patients' carrying angle returned to normal. The radiological union was evident in 8 to 12 weeks in all fractures without complications. Every patient had a good to excellent score on the MEPS and the Flynn criteria. Conclusions: The results of this series indicated a satisfactory outcome in children with delayed more than 14 days of supracondylar humeral fractures. The closed reduction with a minimally invasive technique followed by external fixation is an alternative treatment for such injury.